THE CONNECTION OF ACOUSTIC EMISSION WITH A PROPERTIES DISPERSION OF COMPOSITE MATERIAL MACHINING - Filonenko, Sergii (Proceedings of National Aviation University (archive), 2015)
The results of acoustic emission signals modeling during the composite materials machining for the mechanical model of material’s surface layer destruction in dependence of its properties dispersion is considered. It is shown that variation of composite materials disperse properties does not effect on the nature of acoustic emission. The influence of composite materials disperse properties on acoustic emission amplitude parameters is determined. It is show that with global increase of acoustic emission amplitude parameters the variance of the average level of the resultant acoustic emission signal amplitude has the highest sensitivity.